Deep Vein Thrombosis as a Rare Presentation in a Female With Anti-Neutrophil Cytoplasmic Antibodies-Associated Vasculitis - Wan Syamimee WAN GHAZALI; Nurashikin MOHAMMAD; Asmahan Mohd ISMAIL (Archives of Rheumatology, 2017)
This article aims to report a case of a young female patient with anti-neutrophil cytoplasmic antibodies-associated vasculitis complicated with pulmonary renal syndrome, multiple relapses, and who later developed venous thromboembolism. Pulmonary renal syndrome is a well- recognized and lethal complication; however, incidence of venous thromboembolism has not been well-described. In this article, we described a 38-year-old Malay female patient admitted in 2008 with three-month history of peripheral neuropathy of lower limbs and right ankle ulcers. Initial inflammatory markers were high and perinuclear Anti-Neutrophil Cytoplasmic Antibodies were positive. She was diagnosed as anti-neutrophil cytoplasmic antibodies-associated vasculitis and started on intravenous methylprednisolone with methotrexate. She presented with relapse of skin vasculitis complicated with pulmonary renal syndrome after being stable for one year. She was intubated and proceeded with plasmapheresis and hemodialysis. She completed six cycles of cyclophosphamide. Renal biopsy revealed chronic changes consistent with end stage renal disease. She further relapsed in 2011 with nasal blockage, epistaxis, and nasal deviation. Chest X-ray revealed lung nodules. Prednisolone was increased, her symptoms settled, and she was discharged with azathioprine. She was readmitted at the end of the same year due to two-day history of right deep vein thrombosis and she later succumbed to methicillin-resistant Staphylococcus aureus sepsis.